Basic science review of transcutaneous osseointegration: current status, research gaps and needs, and defining future directions - Bailey V. Fearing, PhD; Ida Leah Gitajn, MD; Sarah M. Romereim, PhD; Jason S. Hoellwarth, MD; Joseph C. Wenke, PhD; Joseph R. Hsu (OTA International)
Abstract. Basic science research is vital for advancing the emerging field of bone-anchored limb replacement (BALR), or osseointegration (OI). This article discusses clinical challenges for BALR/OI, summarizes current basic science research regarding those challenges, identifies research gaps, and proposes future directions. OI research draws from related fields such as orthopaedic implants and dentistry. There is a need for small animal models to study critical questions related to osseointegration, including OI implant-associated infections. Small animal models are also critical to ensuring safety and efficacy of novel treatments in this vulnerable population. Key issues include infection prevention through implant surface modifications, biofilm-targeting technologies, and antimicrobial advancements. The skin–implant portal, unique to BALR, also poses significant challenges. Research on skin attachment and inflammatory processes is crucial. Noninfectious inflammatory loosening of implants, though infrequent, needs further investigation. This review emphasizes the need for collaborative efforts to develop effective preclinical models and innovative infection prevention strategies. Addressing these challenges is essential for optimizing patient outcomes and advancing this emerging field.